The Organization-Public Relations, Situational Factors, and Public Participation in Corporate Social Responsibility: The Moderating Role of Corporate Social Responsibility Motivation - Elvina Yulindra Hazanah; Atikah Nur Fadlilah; Ina Ayu Dya Kusumawati; Alex Johanes Simamora (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
Organizational-public relations and situational factors determine public participation in corporate social responsibility (CSR) programs, and their effectiveness is also determined by corporate motivation. This study aims to examine the influence of organizational-public relations and situational factors on public participation in CSR activities, as well as to examine the moderating role of CSR motivation on the influence of organizational-public relations and situational factors on public participation. This study uses three theories, namely relationship management theory, situational problem-solving theory, and attribution theory to explain how trust, commitment, mutual control, satisfaction, guidance, and problem-solving motivation influence public participation. This study uses online CSR campaigns conducted by Unilever Indonesia and Danone Indonesia. The research sample included 399 respondents who were followers of Unilever Indonesia and Danone Indonesia on social media. The research variables were measured using a 7-point Likert scale questionnaire. Data analysis used the SEM-PLS-based path analysis method. Based on data analysis, this study found that the organization-public relationship and situational factors had a positive effect on public participation in CSR activities. In addition, CSR motivation acts as a moderating variable, where public-serving motivation strengthens, while companies-serving motivation weakens the influence of the organization-public relationship and situational factors on public participation. These findings have important implications for corporate communication strategies in increasing public involvement in social value-based CSR programs.  Keywords: organization-public relations, situational factors, corporate social responsibility participation, corporate social responsibility motivation